The evo‐devo of multinucleate cells, tissues, and organisms, and an alternative route to multicellularity. Issue 6 (November 2013) - Niklas, Karl J.; Cobb, Edward D.; Crawford, David R.
SUMMARY Multinucleate cells, tissues, or organisms occur in 60 families of land plants and in five otherwise diverse algal lineages (Rhodophyceae, Xanthophyceae, Chlorophyceae, Ulvophyceae, and Charophyceae). Inspection of a morphospace constructed out of eight developmental processes reveals a large number of possible variants of multinucleate cells and organisms that, with two exceptions, are represented by one or more plant species in one or more clades. Thus, most of these permutations of developmental processes exist in nature. Inspection of the morphospace also shows how the siphonous body plan (a multinucleate cell with the capacity for indeterminate growth in size) can theoretically serve as the direct progenitor of a multicellular organism by a process similar to segregative cell division observed in siphonocladean algae. Using molecular phylogenies of algal clades, different evolutionary scenarios are compared to see how the multicellular condition may have evolved from a multinucleate unicellular progenitor. We also show that the siphonous progenitor of a multicellular organism has previously passed through the alignment‐of‐fitness phase (in which genetic similarity among cells/nuclei minimizes internal genomic conflict) and the export‐of‐fitness phase (in which genetically similar cells/nuclei collaborate to achieve a reproductively integrated multicellular organism). All that is theoretically required is the evolutionary acquisition of the capacity to compartmentalize its cytoplasm.